Quantifying the Comprehensive and Progressive Agreement for Trans-Pacific Partnership - Dan Ciuriak; Jingliang Xiao; Ali Dadkhah (East Asian Economic Review (EAER), 2017)
We assess the outcomes for the negotiating parties in the Trans-Pacific Partnership if the remaining eleven parties go ahead with the agreement as negotiated without the United States, as compared to the outcomes under the original twelve-member agreement signed in October 2016. We find that the eleven-party agreement, now renamed as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), is a much smaller deal than the twelve-party one, but that some parties do better without the United States in the deal, in particular those in the Western Hemisphere-Canada, Mexico, Chile, and Peru. For the politically relevant medium term, the United States stands to be less well-off outside the TPP than inside. Since provisional deals can be in place for a long time, the results of this study suggest that the eleven parties are better off to implement the CPTPP, leaving aside the controversial governance elements, the implications of which for national interests are unclear and which, in any event, may be substantially affected by parallel bilateral negotiations between individual CPTPP parties and the United States.
Keywords: F02; F13; F15; 330; Trans-Pacific Partnership; TPP; CPTPP; United States; CGE Modelling